Criminal restorative justice in Minas Gerais - Costa, Edgard Gonçalves da (Seven Editora, 2023)
This text aims to investigate the institute of Restorative Justice, a complementary model to the traditional penal system, providing opportunities for the active participation of all. This study is qualitative and descriptive, having as a methodology the review of literature and regulations, in which the institute of Restorative Justice in Minas Gerais is analyzed. It was found that Brazilian courts have promoted this alternative form of conflict resolution. DOI:https://doi.org/ 10.56238/devopinterscie-108